The legacies of Matthew Shepard
1 online resource.
Keywords: This edited collection explores the deeper contexts and consequences surrounding the murder of Matthew Shepard. This young gay man was brutally beaten and left tied to a fence on a chill Wyoming night in October 1998. Found the next morning by two cyclists, he was transported to a hospital in Fort Collins, Colorado where he died five days later. His murder was one of the most publicized and for some, most vividly remembered, instances of hate crime related violence based on sexual orientation. Twenty years after his death, Matthew Shepard's story is at a critical turning point: memories of his murder and its meanings can either fade into the past or be reinvigorated to make up part of more meaningful investigations into LGBTQ and modern U.S. history. The multidisciplinary contributors to this book blend personal narrative with more conventional academic approaches to offer a 20-year retrospective that re-examines the subject of Shepard's murder, whilst also bringing to light questions of historical memory, rurality, race, and public policy. Each of the disciplines and genres included contributes unique understandings of the murder and responses to it that cannot be articulated solely through traditional academic writing. This collection then not only tells the story of Matthew Shepard in the context of 2018, but also provides a compelling view of how and through which means American culture communicates painful histories of violence, bias, and death.